PREVALENCE AND FACTORS ASSOCIATED WITH HUMAN PARVOVIRUS B19 INFECTION IN SICKLE CELL PATIENTS HOSPITALIZED IN TANZANIA - Florence Urio; Humphrey George; Furahini Tluway; Thomas B Nyambo; Bruno P Mmbando; Julie Makani (Mediterranean Journal of Hematology and Infectious Diseases)
Background: The distribution of human parvovirus B19 (HPV B19) infection is ubiquitous and occurs worldwide. The virus has high tropism to red blood cells progenitor`s cells leading to temporary infection of bone marrow and transient arrest of erythropoiesis. People with frequent episodes of haemolytic anaemia including sickle cell disease (SCD) and thalassemia are at increased risk of infection. This study aimed at assessing prevalence and factors associated with HPV B19 infections among hospitalized SCD patients. Methodology: This is a cross-sectional hospital-based study among 329 SCD patients hospitalized at Muhimbili National Hospital (MNH). HPV B19 was detected using RT-PCR. Haematological and Chemistry tests were done using Sysmex XT2000i and Chemistry analyser respectively. Results: The prevalence of HPV B19 among hospitalized 329 SCD patients was 29%. The median age for hospitalized SCD patients with HPV B19 was 15 years (IQR; 7-22), no variation of prevalence with age. In multivariate logistic regression model, HPV B19 infection was associated with pain (OR=4.28, 95%CI: 1.20–15.19; p=0.025), low neutrophil counts (OR=0.57,95%CI: 0.35–0.92, p=0.022) and MCH (OR=0.92, 95%CI: 0.85–0.99; p=0.033). In univariate analysis, HIV infection was slightly higher in SCD patients infected with HPVB19 (exact p-value=0.083). Conclusion: The prevalence of HPV B19 among hospitalized SCD patients at MNH was high. SCD patients with HPV B19 were more likely to present with pain, low neutrophils levels and MCH. HIV infection might be associated with high risk of HPV infection in SCD patients, however this requires further investigation.